PLTS Design for Big Industry Needs - Azarya NJ Siahaan (Journal of Science Technology (JoSTec), 2021)
Solar cell is a device that converts radiation from sunlight into electrical energy directly, which is also called photovoltaic . The Solar Module ( Photovoltaic ), functions to convert solar energy into DC electric current which is forwarded to the Battery Control Unit (BCU) for further storage in the battery. In this research, a solar cell electric power system with a capacity of 10 MW on-grid will be designed for large industrial needs. The performance of a 10 MW on-grid solar cell power system was simulated using RETScreen Clean Energy Project Analysis software , designed by Natural Resources Canada. This research begins with a prefeasibility study of a 10 MW on-grid solar cell power system using RETScreen software which has an extensive database of meteorological data including daily horizontal solar global radiation as well as databases of various components of renewable energy systems from different manufacturers. The technical and financial performance of a 10 MW on-grid solar cell power system was simulated using RETScreen software. This design is expected to be used as a model to develop a Solar Power Generation System (PLTS) network for large industrial needs.